10 kW peak power, single-frequency 1553 nm nanosecond pulsed fiber laser for time-of-flight LIDAR. (1st February 2023) - Zhang, Zhitao; Li, Zheng; Yu, Hanghang; Xuan, Hongwen
Abstract: A 10 kW peak power, 10 ns duration and 6 kHz repetition rate fiber laser system at 1553 nm based on an Er/Yb co-doped large-mode-area fiber, is demonstrated experimentally. The seed laser is provided by a DFB laser switched with a semiconductor optical amplifier. Its optical spectrum, linewidth, and beam quality are measured and discussed. This pulsed laser with short pulse duration and high peak power could be a candidate for the laser source of time-of-flight light detection and ranging (LIDAR).